The cost of diets according to diet quality and sociodemographic characteristics in children and adolescents in Belgium - Camille Pedroni; Stefanie Vandevijvere; Lucille Desbouys; Manon Rouche; Katia Castetbon (International Journal of Food Sciences and Nutrition, 2021)
This study aims to estimate cost variations according to diet quality and sociodemographic characteristics in children. Data (n = 1,596; 5-17 y) from the Belgian National Food Consumption Survey were used. The "Kidmed index" and dietary patterns (DP) identified through principal component analysis were used to assess diet quality. Daily diet cost was estimated after linking the consumed foods with the GfK ConsumerScan panel food prices. The mean diet cost was 4.68€/day (SEM: 0.05). Adjusted for covariates and energy intake, the mean diet cost was 9.1% higher in the highest Kidmed adherence (vs. the lowest) and 6.2% higher in the tercile T3 (vs. T1) of the "Healthy" DP score. It was 4.8% lower in the T3 (vs. T1) for the "Junk food" DP score. Diet cost was higher in 12-17 year-olds (vs. 5-11 years) and in medium and high educated household (vs. the lowest). These findings support policies to make healthy diets more affordable.